Spectrum of Mutations and Long-Term Clinical Outcomes in Genetic Chylomicronemia Syndromes - D’Erasmo, Laura; Di Costanzo, Alessia; Cassandra, Francesca; Minicocci, Ilenia; Polito, Luca; Montali, Anna; Ceci, Fabrizio; Arca, Marcello (Arteriosclerosis, thrombosis, and vascular biology, 2019)
OBJECTIVE:Familial chylomicronemia syndrome (FCS) and multifactorial chylomicronemia syndrome (MCS) are the prototypes of monogenic and polygenic conditions underlying genetically based severe hypertriglyceridemia. These conditions have been only partially investigated so that a systematic comparison of their characteristics remains incomplete. We aim to compare genetic profiles and clinical outcomes in FCS and MCS. APPROACH AND RESULTS:Thirty-two patients with severe hypertriglyceridemia (triglyceride >1000 mg/dL despite lipid-lowering treatments with or without history of acute pancreatitis) were enrolled. Rare and common variants were screened using a panel of 18 triglyceride-raising genes, including the canonical LPL, APOC2, APOA5, GP1HBP1, and LMF1. Clinical information was collected retrospectively for a median period of 44 months. Across the study population, 37.5% were classified as FCS due to the presence of biallelic, rare mutations and 59.4% as MCS due to homozygosity for nonpathogenic or heterozygosity for pathogenic variants in canonical genes, as well as for rare and low frequency variants in noncanonical genes. As compared with MCS, FCS patients showed a lower age of hypertriglyceridemia onset, higher levels of on-treatment triglycerides, and 3-fold higher incidence rate of acute pancreatitis. CONCLUSIONS:Our data indicate that the genetic architecture and natural history of FCS and MCS are different. FCS expressed the most severe clinical phenotype as determined by resistance to triglyceride-lowering medications and higher incidence of acute pancreatitis episodes. The most common genetic abnormality underlying FCS was represented by biallelic mutations in LPL while APOA5 variants, in combination with high rare polygenic burden, were the most frequent genotype of MCS.